The impact of metabolic syndrome on bone mineral density in postmenopausal women - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2012)
Aim: To determine the impact of metabolic syndrome (MS) on dual-energy X-ray absorptiometry (DEXA) derived mean T scores of lumbar vertebra of Turkish women during postmenopausal period. Methods: One hundred and eighty healthy postmenopausal women seen at the University Gynecology or Menopause Outpatient Clinics were enrolled for this cross sectional study. The women were allocated to one of two groups according to the presence or absence of MS. The groups were then compared for bone mineral density (BMD) of the lumbar vertebrae, as measured by DEXA. The Fischer exact test were used for continuous variables and chi-square test was used for categorical variables. Multivariable logistic regression modeling was used to compute the odds ratios of variables predictive of diminished T scores at lumbar area less than -1. Results: The mean T scores for the lumbar area for women with or without MS were comparable either according to National Cholesterol Education Program criteria. Moderate positive correlation was found between T score less than -1 and high density lipoprotein (HDL) cholesterol. Triglyceride/HDL cholesterol and fasting blood glucose showed weak negative correlation with T score less than -1. Conclusions: It appears that MS in postmenopausal women does not have an impact on BMD in our population.
Keywords: Bone density; metabolic syndrome; osteopenia; postmenopause; INSULIN-RESISTANCE; BODY-MASS; RISK; OSTEOPOROSIS; OLDER; PREVALENCE; FRACTURE; HEALTH; LIPIDS; MEN